Targeting of the IGFBP3/TMEM219 pathway restores intestinal stem cells capability of healing mucosa in gastrointestinal autoimmune disorders - Amabile, Giovanni; D’Addio, Francesca; Maestroni, Anna; Zangarini, Monique; Porzio, Stefano; Camboni, Maria Gabriella; Assi, Emma; Petrazzuolo, Adriana; Loretelli, Cristian; Ben Nasr, Moufida; Usuelli, Vera; Abdelsalam, Ahmed; et al. (Pharmacological research, 2025)
Insulin-like growth factor binding protein 3 (IGFBP3) signals through the death receptor TMEM219 to modulate survival of target cells; inhibition of this signaling has been associated with a rescue of intestinal stem cell death. Here we report the screening, generation, and characterization of fully human IgG monoclonal antibodies (mAbs) through phage display or by hybridoma technology, that block IGFBP3 or TMEM219. Both anti-IGFBP3 and anti-TMEM219 mAbs showed high affinity binding with the target antigens and potent effects in protecting self-renewal ability of intestinal stem cells in in vitro relevant assays. Among all the mAbs tested, anti-TMEM219 mAbs generated by phage display, particularly Ent001, showed the highest score in displacing the IGFBP3/TMEM219 binding and in rescuing intestinal stem cells (ISC) markers expression and function in IGFBP3-cultured human mini-guts obtained from healthy donors. In human in vitro proof-of-concept studies, in which we generated mini-guts from patients with immune-mediated intestinal disease such as Crohn’s disease, Ent001 successfully restored mini-guts growth and ISC markers’ expression, while expression of the proapoptotic IGFBP3-related factor Caspase 8 was downregulated. In vivo, in models of DSS-induced chronic colitis and in inflammatory-mediated carcinogenesis, Ent001 significantly improved disease activity index and histological score, restored mucosal morphology and abrogated the development of carcinomas, leading to mucosal healing. In summary, Ent001 represents a novel IGFBP3/TMEM219 inhibitor to be further tested and developed in clinical studies as a novel therapeutic in immune-mediated and inflammatory intestinal diseases. [Display omitted]